Evaluating Public and Regulatory Acceptance for Urban Soil Management Approaches. Issue 1 (1st January 2017) - Obrycki, John F.; Basta, Nicholas T.; Wilson, Robyn S.
Abstract : Regulators ( n = 14) and the public ( n = 30) were surveyed to compare how they perceived contaminated soil management strategies, including bioavailability assessments, using a mental models approach. Both groups proposed similar soil contamination definitions and agreed laboratory tests were needed to identify contaminants. When responding to open‐ended questions about management options, regulators emphasized the risk assessment process, whereas the public noted specific treatment options. The majority of the public (68%) and regulators (86%) were concerned about particular contaminants. The public emphasized general contaminant categories, such as petroleum products and chemicals. Regulators listed specific compounds, including arsenic and dioxin. Both groups mentioned lead. Public and regulators had similar levels of agreement for soil removal ( p = 0.96) and allowing soils with low bioavailability to remain in place ( p = 0.66). The public were most opposed (43% disagree or strongly disagree) to using soil capping. Both groups were willing to consider using bioavailability assessments for contaminated soils. All regulators had heard of bioavailability, whereas 21 of the 24 (88%) public had not heard of this concept. Across all soil management options, the public tended to have higher rates of strongly disagree/disagree and neutral responses compared with regulators ( p = 0.01). The neutral responses may indicate public ambivalence or insufficient information to respond about treatment options. Communication and public education efforts should emphasize the analytical process used to justify site‐specific treatments. Additional surveys should evaluate public and regulator definitions of successful soil management and contaminant remediation in specific situations (i.e., case studies with specific contaminants and receptors of interest). Core Ideas: Bioavailability applications in soil management are a new concept for the public. Public and regulators noted willingness to consider contaminant bioavailability. Public disagreed most strongly with capping as a treatment option.